NARRATIVE TEXT LEARNING THROUGH INFORMATION TRANSFER TEHNIQUE TO INCREASE THE STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Rosmiyati, Evi (Universitas PGRI Palembang, 2021)
The main problem of this study is it effective to teach reading narrative text through information transfer technique to the eight grade students of PGRI 1 Junior High School of Palembang? The objective of this study was to find out whether or not it is effective teaching reading narrative text through information transfer technique to the eight grade students of of PGRI 1 Junior High School of Palembang? The population of this study was the eighth grade students of of PGRI 1 Junior High School of Palembang in the academic years of 2020/2021 which contain 128 students, 32 students as the sample by using cluster random sampling. The method of this research was poor-experimental method and the data were collected through multiple choice. The result of this study showed that students’ average score in the post-test was better than the students’ average score in pre-test. The students’ average score in the pre-test was 38.14, it increased after being given the treatment using information transfer technique the students’ average score in the post-test 61.34 and t-obtained was 5.54, since t-obtained was higher than its critical value, which is (1.684), the null hypothesis (Ho) was rejected while the alternative hypothesis (Ha) was accepted. Therefore, it could be assumed that it was effective to teach reading narrative texts through Information Transfer Technique to the eight grade students of PGRI 1 Junior High School of Palembang.